Exhaled Jet and Viral-Laden Aerosol Transport from Nasal Sneezing - Hana Salati; David F. Fletcher; Mehrdad Khamooshi; Jingliang Dong; Kazuhide Ito; Sara Vahaji; Kiao Inthavong (Aerosol and Air Quality Research)
Abstract The recognition that the spread of COVID-19 is primarily through airborne transmission has brought renewed urgency to understand the spread of aerosols generated from patients. Viral-laden aerosols generated from oral coughs have been well studied; however, aerosols generated from nasal sneezing has been overlooked. This scenario arises from patients who suffer allergenic rhinosinusitis, or the nasal cavity is irritated, particularly during naso-endoscopy. Nasal sneezing is characterised by an explosive blast of air exiting the nostrils, which can be considered as dual jets, resulting in the spread of viral-laden aerosols remaining suspended in the air. This study used computational fluid dynamics consisting of a hybrid RANS-LES turbulence method to model the airflow and the discrete phase model to track aerosol dispersion during nasal sneezing. The results demonstrated that the exhaled airflow jets during nasal sneezing resemble the flow characteristics of two parallel jets in co-flow. These two jets interfere with each other in the merging zone, and after they merge, the sneeze plume expands radially. The nasal sneeze forms a V-shaped plume with smaller particles in the core region. At the end of the sneeze, when the exhaled jets have lost their initial momentum, the large particle dispersion is dominated by gravity. We detected the presence of a ‘sneeze puff’ that transport droplets away from the body, similar to the buoyant puff observed in recent COVID-19 studies of oral coughs.